Facile fabrication of a CoO/g-C3N4 p–n heterojunction with enhanced photocatalytic activity and stability for tetracycline degradation under visible light. Issue 15 (13th July 2017) - Guo, Feng; Shi, Weilong; Wang, Huibo; Han, Mumei; Li, Hao; Huang, Hui; Liu, Yang; Kang, Zhenhui
Abstract : The CoO/g-C3 N4 p–n heterojunction photocatalysts exhibit enhanced photocatalytic activity and stability under visible light. Abstract : Since the misuse and overuse of tetracycline (TC) increase the pollution of aqueous solution, it is highly desirable to develop highly effective, stable, eco-friendly, economical, and facile photocatalysts for the photocatalytic degradation of TC in an aqueous solution. Herein, we designed and synthesized a highly efficient CoO/g-C3 N4 p–n heterojunction via a facile solvothermal method. The experimental results demonstrated that after the coupling of CoO with g-C3 N4, CoO nanoparticles were uniformly distributed on the surface of wrinkled g-C3 N4 layers not only to readily form a p–n heterjunction, but also to avert the aggregation; and the CoO/g-C3 N4 p–n heterojunction photocatalysts exhibited superior visible-light photocatalytic activity and stability for the removal of TC. The high photocatalytic activity could be attributed to the generation of an internal electric field induced by the p–n heterojunctions, effectively promoting the separation of photoinduced charge.